Securing Trading Card Game Assets Using Blockchain Technology - Maciej Rak; Marcin Niemiec (Applied Sciences)
Physical Trading Card Games (TCGs) face inherent challenges, including vulnerability to theft, damage, and counterfeiting. Trading systems primarily depend on third-party marketplaces that collect fees from each trade, without benefiting the game developers. Players also deal with problems associated with shipping, such as high prices, long shipping times, and the risk of counterfeit goods. This paper introduces a blockchain-based solution that decouples card ownership from the physical media, which represents ownership with secure and verifiable digital tokens. The system leverages Ethereum Virtual Machine (EVM), the ERC-1155 standard, and InterPlanetary File System (IPFS) storage, ensuring flexibility, scalability, and cost-efficiency. The adoption of the lazy minting technique minimizes upfront costs for game developers by creating tokens only when acquired by end users. Physical representations of such digital goods can be printed on demand as they remain only a game accessory. The system also provides low-cost exchanges, significantly reducing the financial and logistical burdens associated with the trading of physical assets. Finally, the protocol empowers developers to monetize secondary markets through transaction fees. This approach addresses the limitations of physical card systems and also unlocks new opportunities for innovation and revenue in the TCG ecosystem.